White paper: how Malaysian banks can elevate B40 and MSME lending - Abdul Adzis, Azira; Batten, Jonathan A.; Kosim, Zunarni; Mohamed Arshad, Shamsul Bahrain (2019)
The B40 (Bottom 40% of Household Income) and MSME (Micro Small Medium Enterprise) are a critical component of the Malaysian economy and financial system. They are supported by a complex financial market ecosystem. MSMEs tend to lack financial market and technological sophistication and demand for external financing is driven by mature firms typically older than 5 years. Younger firms rely on personal savings and informal financing networks. There are opportunities in the domestic market for lenders to overcome known supply-side impediments.Malaysia’s situation is not unique. Internationally, while shifting demand and supply side impediments affect MSME access to finance, credit supply side factors dominate. Since most MSMEs are family owned firms, agency considerations may also underpin the preference for external financing by informal or private lenders. However, in the post Global Finance Crisis setting, supply-side impediments have provided the funding opportunity for alternative non-bank financial intermediaries. In the European Union, which has the benefit of a single currency, the alternative finance market is growing. Importantly, participation is characterized by younger and more financial literate and technology savvy borrowers.In Malaysia, well known demand and supply-side impediments along with poor technical infrastructure and financial literacy, especially in remote and agriculturally based areas, limit what is easily achieved in terms of expanding the B40 and MSME loan portfolio. Option-like risk management products could also be made available to reduce earnings volatility and improve credit quality, especially for MSMEs, although these will need to be designed (in the case of Malaysia) to be shariah compliant. Demand side improvements could focus on improving the bank-customer relationship with engagement at the early business stage, while supply side improvements could focus on alternate methods of credit scoring and more granular loan segmentation, especially for urban-based B40 borrowers. Nonetheless, there is still scope for innovative financing solutions for loan book growth using (a) partnerships with digital data providers and Fintech operations; (b) underwriting lending services directly by government; and (c) indirectly through the reevaluation of current regulatory capital requirements that further support B40 and MSME lending. Also, a more activist banking agenda including community outreach could form the centerpiece of any new lending strategy to support a financially inclusive society.